A Comparative Analysis Of The Shadowy Facets Of Cry, The Beloved Country And Beloved: Reconciliation, Biblical Allusion, And Nation Healing - Lyna sabbah; Loubna Sabbah (The Journal of Studies in Language, Culture and Society, 2019)
The aim of this article is to analyse and compare the main themes of Alan Paton’s Cry, the Beloved Country, which belongs to African literature, and Toni Morrison‘s Beloved, which fits in the African-American literature. We have followed a merely comparative analysis to detect the resemblances between the two masterpieces. In their acclaimed novels, Paton and Morrison engage in a revision and a rewriting of the history of their countries, taking it upon themselves to fill historical gaps concerning the Black South Africans and the African-American slaves. They also transmit their dreams and foretell a better future. To achieve their objectives, they employ a similar narrative technique, which includes the use of elements of Reconciliation, Biblical allusion, and Nation Healing. The Latter elements are predetermined and interconnected in a way that leaves more room for joy rather than tragedy.